Differences of Maternal Sociodemographic Characteristics with Term and Preterm Birth Among 17 Hospitals In South Sulawesi - Herman, Sriyana; Syamsuriati; Handayani, Rika; Fitrianingsih, Julia; Alanti; Andriani; Marzila, Mariani; Lestari, Eka; Rusli (YCAB Publisher, 2025)
Background:Maternal sociodemographic characteristics play a crucial role in identifying preterm labor, enabling early intervention to prevent its occurrence and recurrence. Understanding these characteristics can support the development of preventive strategies and improve maternal and neonatal health outcomes. Objective:This study aims to determine whether there are significant differences in the sociodemographic characteristics of mothers experiencing term and preterm labor across hospitals in Makassar City. Method:This study employed an observational analytical design involving 257 mothers who had undergone term and preterm labor in 17 hospitals. Data were collected using the Health Card for Preterm Pregnant Women (KASIHKU) instrument and analyzed through an independent samples t-test to compare means between the two groups. Results:Significant differences were observed in the sociodemographic characteristics between term and preterm labor groups across 11 variables, with five variables showing a p-value < 0.05: Body Mass Index (BMI) (CI95%: 0.44–0.66, p < 0.000), history of preterm labor (CI95%: 0.08–0.23, p < 0.000), presence of flour albus (CI95%: 0.32–0.54, p < 0.000), HIV/AIDS status (CI95%: 0.07–0.00, p < 0.039), and Edinburgh Postnatal Depression Scale (EPDS) score (CI95%: 0.02–0.18, p < 0.009). Conclusion:Maternal sociodemographic characteristics, specifically BMI, history of preterm labor, presence of flour albus, HIV/AIDS status, and EPDS score, show significant differences between term and preterm labor groups. These findings provide a foundation for future research and the development of targeted interventions to prevent preterm labor based on maternal sociodemographic factors. Keywords:Preterm labor; Sociodemographic characteristics; Hospital